PROTOTYPE PENGENDALIAN LAMPU DAN AC JARAK JAUH DENGAN JARINGAN INTERNET MENGGUNAKAN APLIKASI TELEGRAM BERBASIS NODEMCU ESP8266 - Ibrahim, Akip Maulana; Setiyadi, Didik (ISTEK WIDURI, 2021)
Internet of Things (IoT) is a concept with the aim of expanding internet network connectivity that is connected to a global network. The Internet of Things (IoT) can be used to remotely control electronic devices such as lights and air conditioners via the internet. This study aims to create a control device that utilizes internet network technology and uses the telegram application to carry out the control process. There are four control features, namely lamp control which is used to turn on one lamp, the second feature is overall lamp control to turn on all lamps at one time, the third feature controls turning on and off the AC, the fourth feature can monitor lamps and the AC is on or off . The research method used in the manufacture of this control device is the Prototype method, which is considered very suitable for use and this device uses the nodeMCU ES8266 microcontroller. The results of this study are the use of Telegram can help and facilitate users or users in monitoring and controlling lights and air conditioners when not in the house.